University Students’ Perceptions of a CLIL-Based Model in Teaching Aviation English Listening Skills - Chkotua, Maia; Dalakishvili, Elizaveta (European Scientific Journal, ESJ, 2025)
The study investigates university students’ perceptions of using a Content and Language Integrated Learning (CLIL) approach to teach Aviation English listening skills. The integration of content knowledge with language acquisition has gained momentum in English for Specific Purposes (ESP), particularly in aviation training contexts where comprehension of authentic radio communication is critical. A mixed-methods design was employed involving 60 undergraduate aviation students at Georgian Aviation University. Data were collected via a perception questionnaire and semi-structured interviews. Results indicate that the majority of students viewed the CLIL-based approach positively, citing improved comprehension, contextual vocabulary acquisition, and increased engagement. However, some challenges, such as cognitive overload and unfamiliar terminology, were also reported. These findings suggest that CLIL holds promise for Aviation English instruction, provided that pedagogical scaffolding and appropriate materials are in place.